QUALITY OF COPRA MANUFACTURED FROM SUB-STANDARD NUTS - S B. Ratnayake' (International Coconut Community Journal, 1999)
It is well known that copra manufactured from substandard nuts are invariably of poor quality. The reasons that lead to or poor quality are varied, depending on the nature of the defect of the raw material. However, a better understanding of the parameters that cause poor quality can lead to attainment of considerable advantages, through minimization of losses arising from deterioration of quality of the product. Though the copra manufactured out of substandard raw material may not strictly meet with the standards of up-market grades such as "Edible " or the "Milling Superior" (See Sri Lankan Standards for Copra) the losses associated with the conventionally practiced systems are evidently possible to be reduced by using appropriate drying techniques. The trials carried out indicate some variations in preparation of raw material and the drying regimes, suitable for substandard nuts depending on the defect of raw material.